Cruzando los mallkus. Las migraciones bolivianas pendulares durante las grandes crisis salitreras (1914 - 1933) - González Miranda, Sergio (Revista de Historia Social y de las Mentalidades, 2011)
This article analyzes the pendular migratory proces s (especially indigenous) to the saltpeter deposits in Tarapacá; standing out “the great crisi s” of 1930 and the following years, analyzing the return to Bolivia and the feeling of being separated from its roots. It is supported that since the end of the First World War  begins the decline of saltpeter expansion cycle, generating migratory process of la bor attraction and expulsion, in which social drama because of unemployment was a common f actor. In other words, it is set out that saltpeter crisis did not come up in the thirti es, as it is usually admitted in literature specializing in saltpeter industry, or else the wor ldwide nitrate decadence process is started since the beginning of the First World War, so in t he twenties the future of this industry is defined.It is considered, especially in the press and offic ial files, the coupling system, the coming and going of Bolivian workers with their families, especially during the years of crisis between 1914 and 1933, where the unemployment drama  affected thousands of Bolivian people whose had to come back to their original com munities.This article is in keeping with a historical analys is framework that rescues the importance of civilian society in bordering countries relation s, such as Bolivia and Chile, phenomenon that the discipline in foreign affairs rightly call s as "paradiplomacy".
Keywords: Salpeter industry; migratory; bolivian workers; paradiplomacy